Role of male partners in the long-term well-being of women who have experienced severe pre-eclampsia and eclampsia in rural Tanzania: a qualitative study. (4th July 2022) - Mooij, Rob; Kapanga, Ruth R.; Mwampagatwa, Ipyana H.; Mgalega, George C.; van Dillen, Jeroen; Stekelenburg, Jelle; de Kok, Bregje C.
Abstract: Men can be essential sources of support in maternal health, even more so in case of severe acute maternal morbidity (SAMM), affecting 1–2% of childbearing women in low-resource settings. In a qualitative study using semi-structured interviews, we explored the perspectives of nine male partners of women who suffered from (pre-)eclampsia six to seven years earlier in rural Tanzania. Male partners considered their role to be pivotal regarding finances, decision-making in healthcare-seeking and family planning and provided physical and emotional support. After SAMM, households may be affected in the long run. Some men took over their female partner's household duties until up to two years after birth. Providing men with more information on complication readiness and birth preparedness would enable them to extend their role in maternal morbidity prevention. IMPACT STATEMENT: What is already known on this subject? The essential role of male partners in maternal health in low- and middle-income countries is well-studied in relation to its impact on care-seeking behaviour. After childbirth, the long-term role of male partners has not yet been studied. What do the results of this study add? We demonstrated the important role of men during, but also after SAMM. Households may be affected years after women suffered from SAMM. For women with the most urgent support needs, this study suggest that at least some men feel responsible for their partner and have different pivotal roles. What are the implications of these findings for clinical practice and/or further research? Because of their motivation to support their female partner, strategies to reduce recurring complications in subsequent pregnancies should include targeting male partners, for example, by increasing birth preparedness and complication readiness. Further studies should confirm the results from our innovative but small-scale study, as well as investigate the long-term role of male partners after uncomplicated births. Other studies could investigate the separation of couples after SAMM, family planning decisions after SAMM and strategies for involving men and increasing complication readiness and birth preparedness.